Kebijakan Wajib Belajar Pendidikan Madrasah Diniyah Di Kabupaten Pasuruan Dalam Perspektif Teori Struktural Fungsional - Qurrota A'yun; Anshori , Isa (Universitas Negeri Surabaya, 2022)
Delinquency and lack of morals in the learner is a very serious problem considering that the student is the successor of the nation. This laziness does not only occur in big cities but in all regions in Indonesia such as in Pasuruan Regency. Responding to the problem of delinquency and lack of morale in students, the Pasuruan Regency government implemented the mandatory policy of Diniyah Madrasah. This is done so that students in Pasuruan Regency can become the next generation of the nation who are superior and have noble character. Based on this problem, this study aims to examine the enactment of the mandatory policy of Diniyah Madrasah in Pasuruan Regency in the lens of functional structural theory of Talcott Parsons. The results of the study showed that changes in the learning system during thepandemic were reviewed with the functional structural theory of Talcott Parsons through the AGIL function, namely: (1) Adaptation, achieving the problem of delinquency and lack of student morale, the mandatory policy of The Diniyah Madrasah was issued. (2) Goal Attaintment, this policy aims to create the next generation of the nation who are superiorand have a charitable character. (3) Integration, the Government as a party synergizes and cooperates with schools and parents to support the process of implementing this policy. (4), latency, the people are expected to be able to participate in this activity with enthusiasm so that the purpose of enacting the mandatory policy of Diniyah Madrasah in Pasuruan Regency can be achieved.